Technical report: analysis of SIR measles model using Euler's method / Nur Aimi Abdul Aziz, Nurul Amirah Yusof and Nor Farahiyah Rosly - Abdul Aziz, Nur Aimi; Yusof, Nurul Amirah; Rosly, Nor Farahiyah (2016)
SIR model which is in the form of system of ordinary differential equations (ODE) is the best mathematical model in representing the epidemic measles outbreak in a population. The trends of measles spread differs as surrounding differs that will lead to variation of parameters used in the equations hence affect the accuracy of solutions of the SIR differential equations. It is identified that the parameters involved in the SIR model are rate of measles transmission and rate of measles recovery. The main objective of this project is to identify the most accurate SIR model based on various sets of parameters proposed by previous researchers. Euler's numerical method is applied in solving the system of differential equations SIR model and from the calculated solutions, identification of the best parameter of rate of transmission, a and rate of recovery, b that are used in simulating the measles outbreak is made.